2016
DOI: 10.1128/jcm.01818-15
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Whole-Genome Sequencing in Characterizing Acinetobacter Epidemiology and Analyzing Hospital Outbreaks

Abstract: bAcinetobacter baumannii frequently causes nosocomial infections and outbreaks. Whole-genome sequencing (WGS) is a promising technique for strain typing and outbreak investigations. We compared the performance of conventional methods with WGS for strain typing clinical Acinetobacter isolates and analyzing a carbapenem-resistant A. baumannii (CRAB) outbreak. We performed two band-based typing techniques (pulsed-field gel electrophoresis and repetitive extragenic palindromic-PCR), multilocus sequence type (MLST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 111 publications
(155 reference statements)
7
71
0
2
Order By: Relevance
“…These are not the only molecular tools to type isolates, repPCR 30,31 and whole genome sequencing 10 are also gaining ground as potential methods for typing. However, we did not choose these methods for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…These are not the only molecular tools to type isolates, repPCR 30,31 and whole genome sequencing 10 are also gaining ground as potential methods for typing. However, we did not choose these methods for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not perform WGS. Recent studies have shown higher discrimination with WGS than with other methods (24). Since WGS has better discrimination, we advance that, had we used this method, a different number of A. baumannii isolates would have been determined to be due to patient-to-patient transmission.…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). Whole-genome sequencing is increasingly being used in epidemiology and outbreak studies (18)(19)(20) owing to its greater accuracy and reliability than PFGE. However, PFGE remains an easy and economical way to determine clonality.…”
Section: Resultsmentioning
confidence: 99%